Evaluation of the Mechanical Properties of Coconut-Fiber- and Plastic-Fiber-Reinforced Concrete - Soriano Perez, Genesis; Alcivar, Lucrecia Moreno; Valle, Rebeca Castro (Engineering, Technology & Applied Science Research, 2026)
The usage of natural and recycled fibers in order to reinforce concrete was driven by the search for sustainable building materials. This study performs a comparative evaluation of the mechanical behavior of concrete using coconut and Polyethylene Terephthalate (PET) fibers. The concrete is mixed and cured under consistent conditions and each fiber type is evaluated separately within the same standardized base mix formulation to eliminate design variables. The considered dosages (0.5% and 1% coconut and 2% PET) represent practical optimums, determined through workability limits and prior research with the same concrete formulation. A Control Mix (CM) (27.46 MPa, or approximately 280 kg/cm²) was designed with fibers of different dosages acting as additional materials. The results suggest that coconut fibers are more effective than PET fibers as a reinforcing agent. Short Fibers (SFs) (100 mm) at a dosage of 1% exhibited the highest compressive strength, increasing it by 15.0%. In terms of flexural strength, Long coconut Fibers (LFs) (200 mm) at 1% were the most effective, increasing it by 13.7%. In contrast, PET fibers at 2% showed modest compression improvement (4.5%) and slight flexural strength reduction (−0.34%). The effectiveness of coconut fiber is due to its better adhesion to the cementitious matrix and its ability to act as a crack bridge, shifting the failure mode from brittle to cohesive with post-cracking structural integrity. These results show that coconut fiber can be used as a sustainable reinforcement material for nonstructural concrete applications and secondary elements.